Influencia de los rasgos de personalidad en la adherencia al tratamiento de pacientes con Diabetes Mellitus Tipo 2 en un hospital público de Iquitos, 2025 - Idrogo Herrera, Milagros (2025)
Objective: To analyze the relationship between personality traits and treatment adherence in patients with Type 2 Diabetes Mellitus treated at the Regional Hospital of Loreto, 2025. Methods: A quantitative, correlational, and non-experimental study was conducted with a sample of 336 patients diagnosed with Type 2 Diabetes Mellitus. Two instruments were applied (the Personality Self-Assessment Inventory (IATP) and the Morisky–Green Adherence Scale), as well as a sociodemographic questionnaire. Data were processed using SPSS v26 through chi-square tests and binary and multivariate logistic regression, considering p < 0.05 as the significance level. Results: 76.8% of participants exhibited low treatment adherence. The most frequent personality traits were respectful-compulsive (26.8%) and cooperative dependent (16.4%), both significantly associated with better adherence (p = 0.033 and 0.048; OR = 0.11 and 0.12; 95% CI: 0.01–0.84 and 0.01–0.98). In the multivariate model, low adherence was associated with marital status (p = 0.002; OR = 2.57; 95% CI: 1.43–4.63) and with primary and secondary education levels (p = 0.005–0.008; OR = 3.55–4.42). Cluster C showed a significant protective effect (p = 0.012; OR = 0.37; 95% CI: 0.17–0.80). Conclusion: Treatment adherence in patients with Type 2 Diabetes Mellitus was influenced by sociodemographic and psychological factors, particularly compulsive and dependent personality traits.